The performance of the manufacturing sector in Tanzania: Challenges and the way forward - Samuel Wangwe; Donald Mmari; Jehovanes Aikaeli; Neema Rutatina; Thadeus Mboghoina; Abel Kinyondo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Tanzania's industrial sector has evolved through various stages since independence in 1961, from nascent and undiversified to state-led import substitution industrialization, and subsequently to de-industrialization under the structural adjustment programmes and policy reforms. The current development agenda, however, has brought industrial development back to be one of the policy priorities. This paper aims at examining the performance of the manufacturing sector, with particular interest in identifying the emerging manufacturing subsectors, drivers of their success, and challenges for sustained competitiveness. The paper shows that manufacturing growth over the last ten years has helped to sustain GDP growth. The growth in manufacturing notwithstanding, it remains largely undiversified, and vulnerable to variations in agricultural production and commodity prices. The most dynamic subsectors in terms of output growth, export growth, production innovation and product diversity are food products, plastic and rubber, chemicals, basic metal work, and non-metallic mineral products. Nevertheless, the domestic value addition is limited by the dependence of imported intermediate goods, signifying limited inter-industry linkages that are important for promoting domestic manufacturing base and employment. Various technological, financial, policy, and administrative constraints remain unresolved and therefore, limiting faster industrial growth and transformation.
Keywords: O14; 330; manufacturing; exports; emerging firms; Tanzania